A review on sun exposure and skin diseases - Merin, K; Shaji, Merin; Kameswaran, R (Indian journal of dermatology, 2022)
Skin is the thin layer of tissue forming the natural integumentary system of the body that acts as a barrier to protect it from exogenous and endogenous factors that induce undesirable biological responses in the body. Among these risk factors, skin damage triggered by solar ultraviolet radiation (UVR) is an escalating problem in dermatology with an increased incidence of acute and chronic cutaneous reactions. Several epidemiological studies have provided evidence for both beneficial and harmful effects of sunlight, particularly the solar UVR exposure of human beings. Due to overexposure to solar UVR on the earth's surface, outdoor professionals such as farmers, rural workers, builders and road workers are most vulnerable to developing occupational skin diseases. Indoor tanning is also associated with increased risks for various dermatological diseases. Sunburn is described as the erythematic acute cutaneous response in addition to increased melanin and apoptosis of keratinocytes to prevent skin carcinoma. Alterations in molecular, pigmentary and morphological characteristics cause carcinogenic progression in skin malignancies and premature ageing of the skin. Solar UV damage leads to immunosuppressive skin diseases such as phototoxic and photoallergic reactions. UV-induced pigmentation persists for a longer time, called long-lasting pigmentation. Sunscreen is the most mentioned skin protective behaviour and it is the most promoted part of the sun smart message along with other effective skin protection strategies such as clothing, that is, long sleeves, hats and sunglasses.